If anyone could help me with this, with explanation that would be great, thanks
(i) Using an appropriate double-angle formula, express sin(4θ) in
terms of sin(2θ) and cos(2θ).
(ii) Using your answer to part(b)(i) and appropriate double-angle
formulas, derive the formula
sin(4θ) = 4 sin θ cos3 θ − 4 sin3 θ cos θ.
for (i) i've worked out (dunno if right)
sin(4θ) = using terms of sin(2θ) = 2sin(2θ)cos(θ)
using terms of cos(2θ) = 1 - 2sin^2(2θ)
but not sure how they would help for part (ii)
seems to be testing my skills in re-arranging the formulas